“Análisis de aspartato aminotransferasa, hemograma e ionograma en bocachico (ichthyoelephas humeralis) y vieja azul (andinoacara rivulatus) en ecosistemas lóticos de la provincia de los Ríos”. - Catagua Párraga, Mario Andrés (2020)
Freshwater inland fish have become one of the pillars of development and socioeconomic support for countless populations, being the vieja azul and bocachico species the most decisive native species within the loticos of the Los Ríos province. Studies of both species have been carried out, prompting the carrying out of studies such as the analysis of aspartate aminotransferase, hemogram and ionogram in bocachico (Ichthyoelephas humeralis) and old blue (Andinoacara rivulatus) in lotic ecosystems of the province of Los Ríos "In the analysis of Hemogram the variables that showed a significant difference were Erythrocytes in the place factor (P = 0.002) with a value greater than 3.75 ± 0.45 / uL for both species of the Pajarito River. Likewise, the hemoglobin variable also presented a significant difference in the place factor (P = 0.035) with a value greater than 11.05 ± 2.89g / dL for the Camarón River. In the Leukocytes they showed a significant difference in the species factor (P = 0.003), presenting a value of 7.63 ± 1.08 / uL for bocachico. In the case of the remaining variables of the hemogram that are hematocrits, V.C.M, H.C.M, C.H.C.M, lymphocytes and neutrophils did not present significant difference. In the GOT it presented a significant difference (P = 0.0021) with a higher value of 224.67 ± 141.7 U / L in the bocachico species. Then there was a significant difference in the Magnesium variable (P = 0.009) in the Place factor with a value greater than 0.53 ± 0.13 in the Quevedo river site. However, in the sodium variable there was no significant difference. Keywords: Hematic cytometry, metabolic enzyme, hemoglobin, leukocytes, native fish.